Russophone literature - Nadezhda I. Nefedova (RUDN Journal of Studies in Literature and Journalism, 2022)
According to the papers of late 20th and early 21st centuries devoted to the belles-lettres written in Russian, a term “Russian literature” or “Russian-language literature” is used along with another term “Russophone literature.” The different understandings of the word “Russophonia” are presented, the views of scientists on the spatial and temporal boundaries of this phenomenon are studied. Additionally, the author provides and analyzes various classifications that allow the users to determine the text corpus attributable to the Russophone literature, as well as the place of this literature in the modern literary process. Based on the study of relevant works by both domestic and foreign scientists, it was concluded that the term of Russophonia dated back to the times of the Russian Empire's colonial expansion in Central Asia and the Caucasus. The development of national literatures and the ideology of people's friendship during the Soviet period, the collapse of the Soviet Union (when people living in one state became the citizens of different countries) contributed to the development and widespread dissemination of Russophonia. This phenomenon, as well as the Russophone literature, is not limited to the geographical boundaries of the states. It can be also assumed that the “Russophone literature” is fairly synonymous with the expression “Russian-language literature.” Still, the use of the “Russophone literature” is considered to be the most suitable and reasonable in relation to the modern Russian-language literature since, according to a number of researchers, it has no ethnical, political and geographical correlation. It is more neutral and harmonious (for example, when translated into English).